种低聚异麦芽糖的制造方法及其催化剂 (2018)
本发明提供了种以淀粉及其衍生物为原料，酶法生产低聚异麦芽糖的方法，通过将来源于黑曲霉的α-葡萄糖苷酶编码基因组合表达，并由固定化α-葡萄糖苷酶催化合成低聚异麦芽糖和由非水双相体系进行产品-固定化酶的快速分离与再循环。本发明以双相反应体系，加入固定化α-葡萄糖苷酶微球催化生产低聚异麦芽糖，反应完成后固定化酶可自动分配到有机相中，实现固定化酶与产物的分离。本发明具有反应条件温和，无需添加其它交联剂，经济性好，降低生产成本，固定化酶酶活回收率高，操作稳定性好等特点。采用本发明方法得到的低聚异麦芽糖产品，可广泛应用于医药、食品、饲料等重要领域。 The invention provides a method of producing isomalto-oligosaccharide by an enzyme method through taking starch and a derivative thereof as raw materials. The isomalto-oligosaccharide is formed by performing combinational expression on an alpha-glucosidase encoding gene from aspergillus niger and performing catalyzed synthesis on immobilized alpha-glucosidase, and quick separation and recycling of a product-immobilized enzyme mixture are realized by a non-aqueous double-phase system. According to the method, the isomalto-oligosaccharide is catalytically produced by adding immobilized alpha-glucosidase microspheres through the double-phase reaction system; after a reaction, the immobilized enzyme can be automatically distributed into an organi